OPTIMIZATION OF TECHNOLOGICAL SOLUTIONS FOR THE CONSTRUCTION OF WELLS FOR LOW-PRESSURE GAS PRODUCTION - Denis V. Shalyapin; Adelya D. Shalyapina (Известия Томского политехнического университета: Инжиниринг георесурсов, 2023)
Link for citation: Shalyapin D.V., Shalyapina A.D. Optimization of technological solutions for the construction of wells for low-pressure gas production. Bulletin of the Tomsk Polytechnic University. Geo Аssets Engineering, 2023, vol. 334, no. 9, рр. 163-171. In Rus.